Teknik Pendederan Udang Galah (Macrobrachium Rosenbergii) di Instalasi Budidaya Air Payau (IBAP) Probolinggo, Jawa Timur - Nauval Chaidar Zaki; Jonathan David Christmason; Ahmad Farhan Ramanda Janitra; Adel Konkrit Abdinusa; Khalid Nurdiansyah; M. Alfarisi Adinata; M. Ghozy Al Ghifari; M. Faizal Ulkhaq (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
Giant Freshwater Prawn (Macrobrachium rosenbergii) or also known as Giant Freshwater Prawn is a type of crustacean that has the largest size compared to other freshwater prawns. Giant prawns are a freshwater fisheries commodity that has great potential to be developed because it has a high selling value. This Field Work Practice (PKL) activity was carried out at the Brackish Water Cultivation Installation (IBAP) in Probolinggo City, East Java. The results of Field Work Practices (PKL) regarding giant prawn nursery techniques start from preparing nursery ponds, preparing water for rearing media, stocking juveniles, managing water tanks for rearing media, water quality management, feed management, controlling pests and diseases, as well as harvesting and packaging. Water quality measurements include DO with values obtained at 5.1-5.6 mg/L, pH 7.1-8.7, temperature reaching 24-28°C, and salinity ranging from 0-5 ppt. The feed given is Artemia salina, corn bran mixed with flakes in a ratio of 3:1, and commercial feed is in the form of pellets with a frequency of administration twice a day, namely in the morning and evening.